Locking compression plate fixation in humeral shaft fractures: A comparative study to literature conservative treatment. (March 2023) - Capitani, P.; Chiodini, F.; Di Mento, L.; Cavanna, M.; Bove, F.; Capitani, D.; Berlusconi, M.
Highlights: The percentage of fracture healing in Sarmiento's cases is excellent, but it is difficult to be reproduced, and satisfactory results can also be achieved with operative treatment. The incidence of malunions showed in conservative treatment may be completely avoided with ORIF (especially considering the varus deformity in conservative treatment). The function is better in the immediate postoperative period, though we should remark that in the long term the function between the conservative and the surgical treatment is similar. The incidence of postoperative radial nerve palsy is low and the recovery occurs in a reasonable time. Abstract: Introduction: Humeral shaft fractures represent about 3% of all fractures. While there are several treatment options for this type of fractures, there is no evidence in literature showing which is the best one. This study aims at analysing the outcomes for patients with humeral shaft fractures treated with Locking Compression Plate (LCP) fixation in our hospital and comparing them with the outcome for patients conservatively treated (according to data from Pubmed), in order to determine the best treatment option. Materials and Methods: We treated surgically 220 humeral shaft fractures in our department from February 2005 to March 2012 . Seventy-three of them met all the inclusion criteria for this study. All fractures were then classified according to the AO classification. The follow-up considered the radiographic healing of the fracture. All patients were treated with plate fixation (LCP - DePuySynthes Co). At the end of the four-year follow-up, the function was evaluated by means of the DASH score . A systematic review of the literature of the last 20 years was performed on MEDLINE (PubMed). Results: We had 2 infections and 8 patients had postoperative nerve palsy which recovered in average time of 6.7 months. In addition, 4 fractures (5.48%) didn't heal within 6 months and they were considered as nonunions and healed after a second surgery . One of these 4 nonunions was infected . The mean DASH score was 18.24±19.18 . No malunions were found. We identified 13 studies that were eligible for our systematic review. The mean non-union rate found was 17% in 2517 fractures with a follow-up that ranging from 67% to 100% of patients and a primary radial nerve palsy ranging from 0 to 115 patients. Malalignment rate ranged from 12.7 to 42%. Conclusions: After taking into account both the conservative and the surgical treatment, for humeral shaft fractures we suggest the operative treatment, because the patient's function of the upper limb recovers quickly in the immediate postoperative period and the incidence of malunions may be avoided .